2021
DOI: 10.2174/1386207323666200808180527
|View full text |Cite
|
Sign up to set email alerts
|

Nickel(II) Chromite Nanoparticles: An Eco-Friendly and Reusable Catalyst for Synthesis of 2,4-Diamino-6-aryl-pyrimidine-5-yl Cyanides under Ultrasonic Radiation

Abstract: Background: One of the principal factors in the field of research in green chemistry is to drive chemical reactions under ultrasonication as a versatile synthetic tool. Moreover, nanostructured metal salts occupy an important position as low cost, efficient, heterogeneous, and green catalysts in chemical reactions. Pyrimidine has also acquired significance because it is a core structure in a variety of natural and non-natural agents, many of which display versatile biological activities and medical application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…As plenty, previous research studies have revealed the nanostructured metal solids are increasingly popular as valuable and advantageous catalysts in various chemical reactions. Among various inorganic solids, spinel type metal chromite with the general formula AB 2 O 4 with high efficiency, nontoxicity, good stability, low-cost synthesis, and recyclability can be considered suitable heterogeneous catalysts for organic transformations [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…As plenty, previous research studies have revealed the nanostructured metal solids are increasingly popular as valuable and advantageous catalysts in various chemical reactions. Among various inorganic solids, spinel type metal chromite with the general formula AB 2 O 4 with high efficiency, nontoxicity, good stability, low-cost synthesis, and recyclability can be considered suitable heterogeneous catalysts for organic transformations [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%